2021
DOI: 10.21037/jgo-21-824
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of distant metastases and predictive nomograms in colorectal mucinous adenocarcinoma: a SEER analysis

Abstract: Background: We evaluated the metastatic patterns and explored the prognostic value of distant metastasis pattern in patients with metastatic colorectal mucinous adenocarcinoma (MC) using the Surveillance, Epidemiology, and End Results (SEER) database.Methods: Between 2010 and 2015, newly diagnosed colorectal MC patients were selected using the SEER database. Patient prognosis was compared based on the clinicopathological parameters, treatment method, and the site and number of metastatic organs. Cox analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Clinically, early specific symptoms are not obvious, and distant metastases are prone to occur. The disease has a poor prognosis and survival rate and is difficult to cure, thus posing a serious threat to the health of those afflicted ( 33 - 35 ). Surgery remains the first treatment option for this disease, including laparoscopic and open surgery ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, early specific symptoms are not obvious, and distant metastases are prone to occur. The disease has a poor prognosis and survival rate and is difficult to cure, thus posing a serious threat to the health of those afflicted ( 33 - 35 ). Surgery remains the first treatment option for this disease, including laparoscopic and open surgery ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that patients with liver and bone metastasis had signi cantly shorter OS compared with patients without metastasis (P<0.001). Additionally, patients with multi-organ metastases had worse prognosis (P<0.001) compared with patients who had fewer metastases [25]. Creasy et al analyzed the 10-year survival rates of patients with CRCLM following liver resection and discovered that a higher number of liver metastatic lesions (>10) indicated poorer prognosis compared with fewer liver lesions [26].…”
Section: Discussionmentioning
confidence: 99%
“…There was a nomogram for the prognosis of colorectal MAC patients constructed by Lian et al Compared to our nomogram study, this previous study was mainly focused on the pattern of distant metastases, and external validation was absent [ 32 ]. Our study was larger in scale and more comprehensive.…”
Section: Discussionmentioning
confidence: 99%